Lexical Richness in EFL Primary Students’ Writing: Insight from Bilingual Classroom in Indonesia - Istihari (Jurnal Bahasa Asing, 2024)
This study investigates the lexical richness of primary EFL students in a bilingual classroom in Indonesia that focus on three key components: Lexical Density (LD), Lexical Variation (LV), and Lexical Sophistication (LS). Employing a qualitative method, this study involved 18 students, 10 male and 8 female of grade 6 primary level. Eighteen written productions were analyzed using the lexical richness’s framework from Laufer and Nation. The results revealed that male students generally had higher LD and LS scores, with Student 1 demonstrating the highest LD score of 89.83 and LS score of 3.38. Female students, however, excelled in TTR, with Student 17 (male) achieving the highest TTR of 0.88, closely followed by Student 11 (female) with 0.85. These findings suggest gender differences in lexical use, with male students tending toward more content-heavy and sophisticated language, while female students showed greater lexical diversity. It is hoped that English teachers use more varied authentic materials to enhance students' advanced vocabulary and to encourage the diversity of their lexical choices.